Childhood health and educational outcomes after neonatal abstinence syndrome: a systematic review and meta-analysis. - Rees,P; Stilwell,PA; Bolton,C; Akillioglu,M; Carter,B; Gale,C; Sutcliffe,A (The Journal of Pediatrics, 2020)
OBJECTIVE: To systematically review and meta-analyze the association between neonatal abstinence syndrome (NAS) and adverse health or educational childhood outcomes. STUDY DESIGN: An all-language search was conducted across 11 databases between 1/1/75, and 9/3/19, and 5865 titles were identified. Observational studies of children between 28 days and 16 years of age, in whom a diagnosis of NAS was documented, were included. Outcomes included reasons for hospital admissions, childhood diagnoses, developmental outcomes, and academic attainment scores. All studies underwent independent review by two trained reviewers, who extracted study data and assessed risk of bias using the Newcastle Ottawa Tool. RESULTS: Fifteen studies were included comprising 10,907 children with previous NAS and 1,730,213 children without previous NAS, aged 0-16 years. There was a strong association between NAS and subsequent child maltreatment (aOR 6.49 (4.46, 9.45, I2=52%)), injuries and poisoning (aOR 1.34 (1.21, 1.49, I2= 0%)), and a variety of mental health conditions. Studies consistently demonstrated an increased incidence of strabismus and nystagmus among those with previous NAS. Children with NAS also had lower mean academic scores than the control group in every domain of testing across age groups. CONCLUSIONS: NAS is significantly associated with future child maltreatment, mental health diagnoses, visual problems and poor school performance. Due to the necessary inclusion of non-randomized studies, incomplete reporting among studies and likely unadjusted confounding, this review does not suggest causation. However, we highlight associations requiring further investigation and targeted intervention, to positively impact the life course trajectories of this growing population of children.